The coexist comedy tour [videorecording (DVD)] - Fugelsang, John, 1969-; Obeid, Sammy (Comedian); Jensen, Keith Lowell; Kasher, Moshe (Comedian) (2013)
When a Jew, a Christian, a Muslim, a Hindu, a Buddhist, and an atheist walk onto a stage, what in God's name could possibly go wrong? Viewers will discover the uproarious truth. A hilarious concert movie, as well as a behind-the-scenes documentary, it's one religious service viewers won't want to miss. Featuring John Fugelsang, Moshe Kasher, Sammy Obeid, Tapan Trivedi, Tissa Hami, and Keith Lowell Jensen.